2021
DOI: 10.1038/s41598-021-87282-z
|View full text |Cite
|
Sign up to set email alerts
|

The neurodevelopment of delay discounting for monetary rewards in pre-adolescent children

Abstract: Children are found to exhibit high degrees of delay discounting compared with adults in many delay discounting studies, which might be due to the asynchronous development of “bottom-up” and “top-down” neural systems. However, the temporal dynamics associated with the two systems in the development of delay discounting processes are not well known. In this study, we chose two age groups of participants and adopted event-related potential (ERP) techniques to investigate the neural dynamic differences between chi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…Scott et al (2017) found that the relationship between heavy cannabis use and cognition in adult and adolescents was not moderated by age-group or age of initiation. Age effects previously found may simply reflect changes in delay discounting that occur over time (Green et al, 1994;Steinberg et al, 2009;Yu et al, 2021), rather than the heightened impact of cannabis exposure. Furthermore, the magnitude of cognitive deficits associated with cannabis use in youth may have been previously overstated (Scott et al, 2018); positive findings may have reflected residual effects from acute use or withdrawal (Grant et al, 2003;Schreiner and Dunn, 2012), or reflected uncontrolled confounders (National Academies of Sciences, Engineering, and Medicine et al, 2017;Scott et al, 2018).…”
Section: Discussionmentioning
confidence: 87%
“…Scott et al (2017) found that the relationship between heavy cannabis use and cognition in adult and adolescents was not moderated by age-group or age of initiation. Age effects previously found may simply reflect changes in delay discounting that occur over time (Green et al, 1994;Steinberg et al, 2009;Yu et al, 2021), rather than the heightened impact of cannabis exposure. Furthermore, the magnitude of cognitive deficits associated with cannabis use in youth may have been previously overstated (Scott et al, 2018); positive findings may have reflected residual effects from acute use or withdrawal (Grant et al, 2003;Schreiner and Dunn, 2012), or reflected uncontrolled confounders (National Academies of Sciences, Engineering, and Medicine et al, 2017;Scott et al, 2018).…”
Section: Discussionmentioning
confidence: 87%
“…Based on a large number of neuroimaging studies from adolescent animals and humans, it was found that the reason for adolescents is a high-risk population for various addiction problems is that the brain grows non-linearly during the growth process from children to adults. Compared with children and adults, the bottom-up development of the limbic system related to reward processing is too rapid, and the development of the top-down prefrontal cortex related to cognitive control is relatively delayed (10,11), which is an important reason for the high incidence of various addiction problems, including Internet addiction in adolescents (Figure 1). Starting from the neurobiological model of brain development, the relationship between the brain reward system and the cognitive control system of Internet addicts is revealed; that is, whether the Internet addicts have defects in the reward system or the cognitive control system, or whether the development of the two systems is unbalanced, is the key to solving the problem of Internet addiction, especially for adolescents.…”
Section: Neural Mechanisms Implications Of Reward Seeking and Cogniti...mentioning
confidence: 99%
“…Robust evidence shows willingness to wait for rewards increases between childhood and adulthood (de Water et al, 2014;Olson et al, 2007;Ripke et al, 2012;Scheres et al, 2014Scheres et al, , 2006Steinberg et al, 2009;van den Bos et al, 2015;Yu et al, 2021). Willingness to wait increases sharply around age 15-16 (de Water et al, 2014), reaches adult levels by late adolescence (Steinberg et al, 2009), or peaks at age 14 and then declines into adulthood (Scheres et al, 2014).…”
Section: Adolescencementioning
confidence: 99%
“…One study showed that delay length was linked to parietal regions whereas striatal areas were associated with the amount of money on offer (de Water et al, 2017). Finally, studies using electroencephalogram (EEG) recordings and delay discounting tasks have also suggested that electrical activity linked to immediate rewards develops early, whereas signals reflecting waiting for delayed rewards develop later in adolescence (Yu et al, 2021).…”
Section: Adolescencementioning
confidence: 99%